Academics in Exile Networks, Knowledge Exchange and New Forms of Internationalization - Axyonova, Vera; Kohstall, Florian; Richter, Carola (The Academy in Exile Book Series, 2022)
Restrictions on academic freedom, persecution and armed conflict have forced many scholars into exile. So far, the professional trajectories of these scholars and their contributions to knowledge exchange have not been studied comprehensively. The contributors to this volume address the situations and networks of scholars in exile, the challenges they face in their host countries and the opportunities they use. These issues are highly relevant to discussions about the moral economies of higher education institutions and support programs. Although the contributions largely focus on Germany as a host country, they also offer telling examples of forced mobility in the Global South, including both contemporary and historical perspectives.